Synthesis of novel composite fibers coated with ferrihydrite layer - Bondar, Yu. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
New composite fibers were synthesized by in situ deposition of iron hydroxide layer on the surface of modified polypropylene fibers. Data of scanning electron microscopy, X-ray diffraction, and Fourier transform infrared analyses are considered. The obtained results identified the deposited phase as two-line ferrihydrite, which forms a compact layer on fibers' surface.